The thought of Mao Tse-Tung - Schram, Stuart R. 1924-2012 (Contemporary China Institute publications, 1988)
The most general and probably the most lasting expression of Mao Tse-tung's contribution to the Chinese revolution was his thought. Stuart Schram's book examines the unfolding of Mao's ideas, and in so doing sheds light on other aspects of Mao Tse-tung's life and times. The author traces the stages in the formation of Mao's thought from the May Fourth period through the peasant movement, the long years of armed struggle against the Kuomintang and the Japanese invaders, the foundation of a new state, his efforts to devise a 'Chinese road to socialism', the Sino-Soviet split, and the so-called 'Great Proletarian Cultural Revolution'. Professor Schram offers a fascinating and sure-footed analysis of Mao's intellectual itinerary, recognizing the positive value of the participatory and anti-bureaucratic thrust of his thought, and of his efforts to link Marxism with Chinese reality, but underscoring also the irrationality of the Great Leap strategy, and the destructive consequences of the personality cult, which led in the end to a combination of anarchy and despotism